Implementasi Framework Flutter pada Prototype Interface Aplikasi Reservasi Terapis Baby Spa - Alfiah, Nur Rizqi; Carudin, Carudin; Purnamasari, Intan (Jurnal Ilmiah Wahana Pendidikan, 2024)
Baby spa can help toddlers experience good growth and development. Because in a baby spa there are lots of stimuli given to make the baby sleep better. Sleep itself influences growth by increasing the production of growth hormone secretion by as much as 75%. Baby spa can be done by parents or baby spa therapists. However, based on the results of pre- research observations, it was found that some parents had difficulty finding baby spa therapy. Seeing the urgency of parents and baby spa therapists in the field of communication technology, there is an opportunity to build a system that can integrate the needs of parents and therapists. Applications available on the Play Store usually only focus on recording baby growth and development, so services for baby spa therapists are very rare and there are not many therapists available. This research produces output in the form of a proposed interface design for baby spa therapy reservation applications that have passed the stages of cutting or coding the application display. This research is said to be successful because the results of testing with users show a value of 89.5 or have an Acceptable Excellent category.